Biofuel Burning Influences Refractory Black Carbon Concentrations in Seasonal Snow at Lower Elevations of the Dudh Koshi River Basin of Nepal - Khan, Alia L.; Rittger, Karl; Xian, Peng; Katich, Joseph M.; Armstrong, Richard L.; Kayastha, Rijan B.; Dana, Jacob L.; McKnight, Diane M. (Frontiers in Earth Science, 2020)
When deposited on snow and ice, light absorbing impurities (LAIs) such as dust and black carbon (BC) reduce surface albedo and enhance melt. BC comes from incomplete combustion of fossil fuels and biomass. Local and regional sources of BC exist in High Mountain Asia, such as dry-dung burning for heat and fuel, which occurs in close proximity to snow and glaciers. Local dust or dust transported from the Indo-Gangetic Plain is also present. In the Ganges River Basin, meltwater is dominated by seasonal snow, yet relatively few observations of impurities in seasonal snow exist. To understand sources of impurities and their concentrations for seasonal snow on land, we evaluated multiple lines of evidence to scale up from ground-based measurements in the Dudh Koshi River Basin, a remote headwater basin within the Khumbu Region of Nepal. We obtained ground-based in-situ observations of refractory black carbon (rBC) measured by Single Particle Soot Photometer (SP2), including size distributions in snow on land. We interpreted these results in the context of concurrent Moderate Imaging Spectroradiometer (MODIS) satellite observations and speciated aerosol optical depth derived from reanalysis products modeled with the Navy Aerosol Analysis Prediction System (NAAPS) global aerosol model. We collected snow samples, mostly in the Gokyo Valley, at varying distances from local tea houses along a 2000 meters above sea level (m.a.s.l) elevation transect from 3250 to 5299 m.a.s.l . rBC concentrations ranged from 3.9 to 76.8 µg-rBC/L-H2O. Although previous data do not exist at these lower elevations, our findings are higher than previous surface snow results at higher elevations in the nearby Khumbu Valley. In general, rBC concentrations were lower in fresh snow than aged snow; concurrent MODIS satellite observations of snow albedo also show smaller impacts from LAIs in visible wavelengths in fresh snow. rBC decreased with elevation in aged snow samples, as did concurrent MODIS albedo observations. rBC-particle size distributions also shifted to a larger mode for aged snow samples. Results from NAAPS indicate anthropogenic and biogenic fine aerosols from biofuel (dry-dung burning) are primary aerosol species for the study period, at ~thrice the concentration of dust and smoke.